Robotics and automation technology for the plantation crops - Wan Ismail, Wan Ishak; Bardaie, Mohd Zohadie (Universiti Putra Malaysia, 1999)
It is envisaged that the effect of labour shortage in the plantation industry can be reduced by increasing productivity of existing labour through mechanization. By introducing the robotic technology, coupled with computer control to automate the robot arm more manpower can be reduced. Robotics technology in plantation industry is still new and still under research and development stage. The complexity of the sensors, actuators and their working environment to make robot withstand bad weather, dust and other adverse conditions have led to a new concept for the agricultural machinery designers. The agricultural robot for plantation crops uses portable hydraulic power source or hydraulic oil available from the tractor. With the use of computer control system softwares, interface hardwares, solenoid valves and other hydraulic components, the robot was able to move the manipulator to harvest and collect agricultural products. Research on camera vision was also carried out.